Pengaruh Disiplin Kerja, Psychological Capital, dan Burnout Terhadap Kinerja Anggota Satuan Intelkam Polres Kediri - Wulan Utami, Rahmawati; Earlyanti, Novi Indah; Prianggono, Jarot (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
In the era of the Industrial Revolution 4.0, the performance of the National Police, especially the Intelligence and Security Unit, is very important for maintaining public security and order. The increasing work demands in securing the stages of the General Election and Regional Election are one of the main challenges faced by the members of the Intelkam Police Resort of Kediri. The performance of the members can be influenced by several factors, including work discipline, psychological capital, and burnout. Work discipline is adherence to rules and procedures, and psychological capital is related to optimism and mental resilience. Burnout is physical and emotional exhaustion due to high work pressure. Therefore, the objective of this research is to determine the influence of work discipline (X1), psychological capital (X2), and burnout (X3) on the performance (Y) of the members of the Intelkam Unit of the Kediri Police. This research uses a quantitative approach with a survey method conducted on all members of the Satuan Intelkam Polres Kediri, totaling 83 respondents. The data analysis technique was preceded by conducting an instrument test, classical assumption test, and hypothesis test by calculating the multiple linear regression value, which resulted in the regression equation: Ŷ = 2.769 + 0.151X1 + 0.701X2 - 0.002X3. In the analysis of the research data, it shows that work discipline and psychological capital partially have a positive and significant effect on performance, while burnout has a negative effect on performance. The t-test value for work discipline, 13.477, is greater than the t-table value of 1.66342, and the t-test value for psychological capital, 16.475, is also greater than the t-table value. This indicates that both variables significantly affect performance. The adjusted R square value of 76.6% indicates that work discipline, psychological capital, and burnout affect the performance of the members of the Satuan Intelkam Polres Kediri.